(-15)+g=(-5)

Simple and best practice solution for (-15)+g=(-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-15)+g=(-5) equation:


Simplifying
(-15) + g = (-5)
-15 + g = (-5)
-15 + g = -5

Solving
-15 + g = -5

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + g = -5 + 15

Combine like terms: -15 + 15 = 0
0 + g = -5 + 15
g = -5 + 15

Combine like terms: -5 + 15 = 10
g = 10

Simplifying
g = 10

See similar equations:

| (2c+9)(c+5)= | | f(x)=6x^3+8x^2+3 | | 6(1-2x)-x=-46 | | B-17=-38 | | 6+2x=5-(7x) | | J+13=37 | | a^2+4ab+4b^2=0 | | M+(-10)=(-2) | | -3a+8=2 | | 4x-3y=52 | | (-17)=(-9)+q | | f(x)=a^3-3a^2-9 | | 2.25=3/4(b-5) | | 17+n=4 | | 6x-x^2+16= | | (-22)+j=(-24) | | 72.8=7(m+3.1) | | 4x+23=75 | | (2c+9)x(c+5)= | | 3[m-1.2]=9 | | h-8+2(h-8)=72 | | 47=19-4x | | 39+x=30+2x | | R-20+4=18 | | 1521=39p+390 | | M+52=53 | | 14y+6(4-8y)= | | y-1/3x=0 | | D-35=50 | | 10(0.6x+4)=10(0.3x+7) | | 2x/(x-3)=8 | | 1521=39(p+10) |

Equations solver categories